Strengthening of MSMEs and Poverty Reduction in Makassar City - Sapriyadi, Sapriyadi; Syaiful, Muhammad; Mujahida, Ummul (Jambura Equilibrium Journal, 2025)
Makassar City, one of Indonesia's big cities, still faces poverty. The poverty data published by the Central Statistics Agency (BPS) shows that over the last decade (2010-2023), the average percentage of poverty decreased very small, only around 0.06%, and the number decreased by only about 124 people. This research aims to find out how the strengthening of MSMEs is carried out by the Makassar City government, as well as how it impacts poverty alleviation. The respondents in this study were 102 MSME actors registered with the Cooperatives and SMEs Office. The analysis method uses a quantitative descriptive and explanatory approach with a binary logistic regression model. The results of the descriptive analysis show that MSME actors who have per capita expenditure above the poverty line are more than those who have per capita expenditure below the poverty line. Efforts to strengthen MSMEs are carried out through collaboration between local governments and state-owned banks, startups, and marketplaces through several trainings, including marketing and digital financial management. The variables of training and Labor have a significant effect on poverty alleviation, while the variables of business credit do not affect poverty alleviation. MSME actors who participated in more than one training 17 times had a per capita income above the poverty line compared to MSME actors who did not participate in training. MSME actors who use Labor 9 times have a per capita income above the poverty line compared to MSME actors who do not use Labor.